Pengaruh Penggunaan Dana KIP-K Terhadap Pemenuhan Kebutuhan Mahasiswa Dalam Prespektif Ekonomi Islam (Studi Pada Mahasiswa Penerima KIP- K UIN Raden Intan Lampung) - Rani Winata; Rifa Khairunnisa (Business and Enterpreneurship Journal (BEJ), 2023)
This study aims to determine how much influence the use of KIP-K scholarship funds has on Fulfilling Student Needs. This research is motivated by the increasing use of the internet over the last year since the pandemic, we need to know the actual realization in the field regarding the use of digital technology to increase financial literacy towards Islamic financial inclusion during the Covid-19 pandemic. The method used in this research is quantitative through a quantitative descriptive approach. Data collection used observation, interviews, questionnaires with research samples of students receiving KIP-K UIN Raden Intan Lampung and documentation. The results of the study show that the use of kip-k scholarship funds has a positive and significant effect on meeting student needs. It is known that 45.9% and the remaining 54.1% are influenced by other variables not examined. This means that these results provide evidence that with good and planned use of the kip-k scholarship funds, it will be able to meet the needs of students both in terms of education and daily life. Seeing the results above, the use of kip-k scholarship funds has been put to good use by students receiving kip-k scholarships, so that they can meet student needs, but it is still not optimal because there are still problems that arise in the student environment. And it is hoped that student heads will be more optimal in using the scholarship funds obtained and remain enthusiastic in learning so that they can improve and maintain their academic achievements. Keywords: Use of Funds, Fulfillment of Needs